A rare presentation of jejunal GIST: A case report - Kalita, Pranjit; Gupta, Arnab; Sengupta, Piyas; Bhattacharyya, Samir (Indian Journal of Case Reports, 2024)
Gastrointestinal stromal tumors (GISTs) are rare tumors that constitute 1% of all GI tract tumors. Jejunal GISTs are the rarest subtype. We present a middle-aged gentleman, who presented with pain in the right lower abdomen. On abdominal examination, a lump was palpable in the right iliac fossa (RIF). Contrast-enhanced computed tomography of the abdomen revealed an extraluminal soft-tissue mass in the ileum. Computed Tomography-guided core needle biopsy from the lump was consistent with GIST, which was confirmed on immunohistochemistry. Mutation analysis revealed exon 11 mutations. Due to the proximity of GIST to the rectum and urinary bladder, the patient was started on imatinib therapy. After 3 months of treatment, imatinib therapy had to be stopped due to skin reactions. Restaging was done with a positron-emission tomography scan, which demonstrated a soft-tissue mass likely arising from the ileocecal region in the RIF abutting the ascending colon without any significant decrease in size. On exploration, a well-circumscribed mobile extraluminal lobulated mass was seen arising from the antimesenteric border of the jejunum. Histopathologic examination showed GIST, which was confirmed on immunohistochemistry. We report this case to emphasize keeping small bowel GIST as an unusual differential diagnosis of a RIF lump. Furthermore, not all patients can tolerate imatinib treatment, hence exon mutation study is important, and surgery should be considered if it is deemed resectable.